How hydrological factors initiate instability in a model sandy slope. Issue 23 (16th October 2013) - Terajima, Tomomi; Miyahira, Ei‐ichiro; Miyajima, Hiroyuki; Ochiai, Hirotaka; Hattori, Katsumi
Abstract Knowledge of the mechanisms of rain‐induced shallow landslides can improve the prediction of their occurrence and mitigate subsequent sediment disasters. Here, we examine an artificial slope's subsurface hydrology and propose a new slope stability analysis that includes seepage force and the down‐slope transfer of excess shear forces. We measured pore water pressure and volumetric water content immediately prior to a shallow landslide on an artificial sandy slope of 32°: The direction of the subsurface flow shifted from downward to parallel to the slope in the deepest part of the landslide mass, and this shift coincided with the start of soil displacement. A slope stability analysis that was restricted to individual segments of the landslide mass could not explain the initiation of the landslide; however, inclusion of the transfer of excess shear forces from up‐slope to down‐slope segments improved drastically the predictability. The improved stability analysis revealed that an unstable zone expanded down‐slope with an increase in soil water content, showing that the down‐slope soil initially supported the unstable up‐slope soil; destabilization of this down‐slope soil was the eventual trigger of total slope collapse. Initially, the effect of apparent soil cohesion was the most important factor promoting slope stability, but seepage force became the most important factor promoting slope instability closer to the landslide occurrence. These findings indicate that seepage forces, controlled by changes in direction and magnitude of saturated and unsaturated subsurface flows, may be the main cause of shallow landslides in sandy slopes. Copyright © 2013 John Wiley & Sons, Ltd.